Effect of peracetic acid used as single irrigant on the smear layer, adhesion, and penetrability of AH Plus - Katia Cristina KEINE; Milton Carlos KUGA; Fernanda Borges Cunha TORMIN; Ana Carolina VENÇÃO; Marco Antonio Hungaro DUARTE; Gisselle Moraima CHÁVEZ-ANDRADE; Gisele FARIA
Abstract The aim of this study was to evaluate the effect of peracetic acid (PAA) as a single irrigant on the smear layer, on the intraradicular dentinal bond strength, and on the penetrability of an epoxy-based resin sealer into the dentinal tubules. A total of 120 roots were distributed into 4 groups according to the irrigant used in root canal preparation: 1% PAA (PAA); 2.5% NaOCl followed by final irrigation with 17% EDTA and 2.5% NaOCl (NaOCl-EDTA-NaOCl); 2.5% NaOCl (NaOCl); and saline solution (SS). The smear layer was evaluated using scanning electron microscopy. The bond strength of an epoxy-based resin sealer (AH Plus) to root dentin was evaluated by the push-out test and penetrability of the sealer into dentinal tubules was observed by confocal laser microscopy. The results were analyzed by the Kruskal-Wallis and the Dunn post-test (α = 0.05). The use of 1% PAA as single root canal irrigant provided smear layer removal and improved the penetrability and bond strength of AH Plus to root dentin in a manner similar to that of the NaOCl-EDTA-NaOCl group (p > 0.05). The NaOCl and SS groups had higher values of smear layer and lower values of sealer penetrability and dentin bond strength than the PAA and NaOCl-EDTA-NaOCl groups (p < 0.05). Thus, 1% PAA has the potential to be used as a single irrigant in root canals.